Characterization of Vibrio parahaemolyticus isolated from clinical specimens and oysters in Thailand - Nipaporn Tewawong; Siriporn Kowaboot; Sudaporn Kengkarn; Unchana Thawornwan; Pongrama Ramasoota; Orasa Suthienkul (Journal of Infection in Developing Countries)
Introduction: Vibrio parahaemolyticus is a common pathogen that can cause seafood-borne gastroenteritis in humans. We determined the prevalence and characteristics of V. parahaemolyticus isolated from clinical specimens and oysters in Thailand.